The Role Of Government In Promoting The Growth Of The Halal Logistics Industry: A Systematic Literature Review From The Perspective Of Islamic Development Economics - Abiyajid Bustami; Purwanti; Isna Yuningsih; Andi Martina Kamaruddin; Rabiatul Adawiyah (Al-Musthofa: Journal of Sharia Economics, 2026)
The Role Of Government In Promoting The Growth Of The Halal Logistics Industry: A Systematic Literature Review From The Perspective Of Islamic Development Economics. This study examines the strategic role of government in the development of halal logistics through a Systematic Literature Review (SLR) of studies published between 2021 and 2025, applying PRISMA-based selection criteria to ensure the reliability and comprehensiveness of the review. The findings reveal a significant gap between the conceptual frameworks advocating government involvement in halal logistics and the fragmented, often underdeveloped, real-world policy implementation. Although literature widely acknowledges the importance of state intervention through regulation, infrastructure, education, and financing, actual practices in many Muslim-majority countries remain uncoordinated and inconsistent. This study integrates developmental state theory with Islamic economic principles and proposes a halal logistics policy framework aligned with national development strategies. Strengthening halal logistics governance requires coordinated government action, positioning it as a strategic instrument for inclusive and ethical Islamic economic transformation.